New early late Miocene species of Vishnuonyx (Carnivora, Lutrinae) from the hominid locality of Hammerschmiede, Bavaria, Germany. Issue 3 (4th May 2021) - Kargopoulos, Nikolaos; Valenciano, Alberto; Kampouridis, Panagiotis; Lechner, Thomas; Böhme, Madelaine
ABSTRACT: This study presents a new species of a large-sized lutrine from the upper Miocene hominid locality of Hammerschmiede, Vishnuonyx neptuni sp. nov., reporting the first occurrence of the genus in Europe and its most northern and western record. The new species differs from the already known members of the genus in size (intermediate between the African Vishnuonyx ? angololensis and the Asiatic Vishnuonyx chinjiensis ) and morphology, in particular in the larger P4 hypocone, the primitive morphology of M1 (paraconule present, enlarged protoconule and metaconule, labial expansion at the paracone area), the shorter and more robust lower premolars and the wider m1 trigonid. We hypothesized that the dispersal event that led to the expansion of the genus in Europe seems to be correlated with the water connection between Paratethys and the Mesopotamian Basin during the Konkian, between 13.4 and 12.65 Ma. In terms of paleoecology, it is here suggested that this form was feeding mainly on fish and less on bivalves or plant material, resembling the extant giant otter, Pteronura brasiliensis .